FRI0290 Identification of at Risk Patients for Cardiac MRI Determined Sub-Clinical SSC-Cardiomyopathy (CM). (15th July 2016) - Bissell, L.-A.; Erhayiem, B.; Hensor, E.; Fent, G.; Greenwood, J.P.; Plein, S.; Andrews, J.; Buch, M.H.
Abstract : Background: SSc-CM carries a poor prognosis once clinically evident. No clear management algorithm to guide screening & investigation for SSc-CM exists. Objectives: To describe cardiac MR (CMR) abnormalities in SSc pts free of CM/CVD & their association with disease (dis.) phenotype to identify the "at risk" pt. Methods: We compared 35 pts with ACR/EULAR criteria SSc & no diabetes/clinical CVD who received SSc/cardiovascular (CV) profile & pulse wave velocity (PWV) assessment & 3T delayed enhancement-CMR reported by CMR-cardiologists to 30 healthy controls (HC). Univariate analysis variables (var.): CV traditional risk factors (TRF), waist/hip ratio (WHR), dis. duration, prev. digital ulceration (DU), known ILD, palpitations hx, dis. subtype, ACA, Scl70, MRSS, NFC, prev. use of cyclophosphamide, SHAQ, FVC, PASP & PWV. Results: Mean (SD) age (yrs) SSc pts 55 (13), 74% female; HC 50 (15), 63% female. Median (IQR) yrs from 1st non-RP symptom 9.5 (2.3, 19.6); 43% dcSSc, 31% ACA+ve, 34% Scl70+ve, 43% known ILD, 37% DU, 0% pulmonary hypertension, 29% prev. use of cyclophosphamide. CMR markers of fibrosis were increased in SSc: ECV (31% SSc vs 25% HC, p<0.001 after adj. for age/sex/TRFs); late gadolinium enhancement (LGE) in 9 SSc vs 1 HC. In SSc, diastolic dysfunction was evident (reduced torsion p0.038), there was a trend for reduced LV mass & RVEF was unexpectedly increased (p=0.028) vs HC. Higher ECV in SSc was associated (ass.) with DU (r0.397 p0.22), decreasing WHR (r-0.510 p0.004) & decreasing TC/HDL (r-0.376 p0.037); none significantly ass. in multi-variable analysis with age/sex. LGE was significantly ass. with ILD (78% vs 33%, p0.047), absence of ACA (0% vs 42%, p0.032), reduced sysBP (mean diff. (95%CI) -14 (27, -1)mmHg p0.034) & lower BMI (mean diff. (95%CI) -4.13 (-8.24, -0.02), p0.049). Other SSc LGE observations: male gender (56% vs 17% LGE-ve), 56% (vs 38% LGE-ve) dcSSc, 56% (vs 29%) Scl70+ve & shorter dis. duration (median (IQR) 7.4 (1.2, 15.8) vs 10.9 (2.5, 19.7) yrs). Conclusions: This study reports CMR detected sub-clinical SSc-CM with detailed SSc phenotype, associating with poor prognostic factors. These data indicate an at risk group for further evaluation that would justify more intensive monitoring for SSc-CM & its complications. The association of ECV with lower lipids/WHR, & LGE with lower BMI/sysBP is new & we postulate may reflect cachexia/medication use in severe disease. Disclosure of Interest: None declared